2008
DOI: 10.1021/ie800377n
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Catalytic Evaluation of Cobalt-Based Monolithic and Powder Catalysts for Fischer−Tropsch Synthesis

Abstract: Cobalt-based monolithic and powder catalysts for Fischer-Tropsch synthesis were prepared. The aluminasupported catalysts contained cobalt (18.6 ( 0.9 wt %) and rhenium (1.2 ( 0.1 wt %) as active phases. To ensure the comparability of both catalysts, monolithic and powder catalysts were prepared from the same CoRe/γ-Al 2 O 3 active powder. While the monolith was prepared by dip coating, the slurry for the coating procedure was also used for preparation of the powder catalyst. It could be shown that both catalys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 24 publications
4
27
0
Order By: Relevance
“…The preparation method for C1 was described in detail by Guettel et al [16]. For C2 and C3, c-alumina particles with diameters of ca.…”
Section: Catalyst Preparation and Characterizationmentioning
confidence: 99%
“…The preparation method for C1 was described in detail by Guettel et al [16]. For C2 and C3, c-alumina particles with diameters of ca.…”
Section: Catalyst Preparation and Characterizationmentioning
confidence: 99%
“…Wedler et al (2009) have reported that the point of zero surface charge (pH pzc ) for purealumina as 7, whereas for Pd/Al 2 O 3 as 8. Guettel et al (2008) studied the zeta potentials of the base materials and catalysts and reported that, for a given pH, the absolute zeta potential of the metal impregnated powder was less then the zeta potential of unimpregnated powders. The decrease in zeta potential leads to agglomeration and gellation of catalytic slurries.…”
Section: Washcoating Of Pd/al 2 O 3 Powdermentioning
confidence: 99%
“…To increase the structural integrity and stability of the slurry, binders have been used (Arnby et al, 2004;González et al, 2007;Guettel et al, 2008;Sánchez et al, 2009). In the present study, colloidal alumina or dispersible pseudo-boehmite (Disperal P2) was used as the binders.…”
Section: Washcoating Of Pd/al 2 O 3 Powdermentioning
confidence: 99%
“…6,7 Recent measurements during Fischer-Tropsch synthesis showed enhanced reaction rates for a fixed-bed reactor with monolithic catalyst in the Taylor flow regime as compared to a stirred tank reactor with suspended powder catalyst. 8 Furthermore, higher C5-C18 liquid fractions are obtained by conducting the Fischer-Tropsch reaction in a monolith catalyst with straight flow channels rather than a packed-bed of catalyst particles. 9 These results are attributed to the advantageous mass transfer characteristics of the monolith reactor in the Taylor flow regime.…”
Section: Introductionmentioning
confidence: 99%
“…Squalane is a viscous liquid and as an inert species serves as good solvent for Fischer-Tropsch products. 8,24 In the experiments, the gas and liquid superficial velocities are in the ranges of 0.05-0.2 m/s and 0.017-0.1 m/s, respectively. High-speed video camera images are used to roughly estimate the axial length of a unit cell and the gas holdup within the unit cell.…”
Section: Introductionmentioning
confidence: 99%